The landscape of global research on diabetic neuropathy - Tavakoli, Mitra; Klingelhöfer, Doris; Fadavi, Hassan; Groneberg, David A. (Frontiers in Endocrinology, 2023)
Diabetic neuropathy (DN) is a prevalent and debilitating complication of diabetes, imposing a significant burden on individuals and healthcare systems worldwide.This study presents a comprehensive analysis of the global research landscape in DN, aiming to provide scientists, funders, and decision-makers with valuable insights into the current state of research and future directions. Through a systematic review of published articles, key trends in DN research, including epidemiology, diagnosis, treatment strategies, and gaps in knowledge, are identified and discussed. The analysis reveals an increasing prevalence of DN alongside the rising incidence of diabetes, emphasizing the urgent need for effective prevention and management strategies. Furthermore, the study highlights the geographical imbalance in research activity, with a majority of studies originating from highincome countries. This underscores the importance of fostering international collaboration to address the global impact of DN. Key challenges and limitations in DN research are also discussed, including the need for standardized diagnostic criteria, reliable biomarkers, and innovative treatment approaches. By addressing these gaps, promoting collaboration, and increasing research funding, we can pave the way for advancements in DN research and ultimately improve the lives of individuals affected by this debilitating condition.